Convergent genomic signatures of domestication in sheep and goats - Florian J. Alberto; Frédéric Boyer; Pablo Orozco-terWengel; Ian Streeter; Bertrand Servin; Pierre de Villemereuil; Badr Benjelloun; Pablo Librado; Filippo Biscarini; Licia Colli; Mario Barbato; Wahid Zamani; et al. (Nature Communications, 2018)
The sheep and goat were domesticated ~10,500 years ago in the same region of the Middle-East. Here, Alberto et al compare the genomes of wild Asiatic mouflon and Bezoar ibex with that of domestics from local, traditional and improved breeds and find common targets of selection related to domestication and improvement in sheep and goats.